Structural, optical and electrochromic properties of cerium dioxide thin films prepared by sol-gel dip coating method - Gokdemir, F. Pinar; Saatci, A. Evrim; Ozdemir, Orhan; Keskin, Bahadir; Kutlu, Kubilay (ELSEVIER SCI LTD, 2015)
Deteriorated crystallite size of the cerianite phase of cerium dioxide thin films prepared by ethanolic sal was restored via annealing. Degree of restoring was monitored through band gap values of the films calculated using UV visible transmission experiments and intercalated/deintercalated charge capacity using cyclic voltammetry. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Ceria; Passive on storage layer; Crystalline size; EPITAXIAL-GROWTH; CEO2; LAYERS; TEMPERATURE; DEPOSITION; DEVICES; SIZE; Engineering; Materials Science; Physics